2015
DOI: 10.3892/etm.2015.2621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin K2 on the development of stress-induced osteopenia in a growing senescence-accelerated mouse prone 6 strain

Abstract: Abstract. Vitamin K2 (VK2) has been used as a therapeutic agent for osteoporosis, since it has been suggested to be able to reduce the frequency of fractures by improving bone quality; however, bone turnover is strictly regulated by various cytokines and hormones. In the present study, the effect of menaquinone-4 (MK-4) on bone turnover was investigated using the senescence-accelerated mouse prone 6 (SAMP6) strain. Since water-immersion restraint stress (WRS) causes a significant decrease in bone mineral densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…However, WNT5A is usually considered to promote osteoclast differentiation and prevent adipocyte differentiation (26). Genistein alone (27) and MK-4 alone (28,29) reportedly promote bone formation; however, in the current study, their co-administration appeared to be more beneficial as it allowed the maintenance of NOTCH2 and WNT5A mRNAs at the levels observed in the control cells.…”
Section: ------------------------------------------------------------contrasting
confidence: 55%
“…However, WNT5A is usually considered to promote osteoclast differentiation and prevent adipocyte differentiation (26). Genistein alone (27) and MK-4 alone (28,29) reportedly promote bone formation; however, in the current study, their co-administration appeared to be more beneficial as it allowed the maintenance of NOTCH2 and WNT5A mRNAs at the levels observed in the control cells.…”
Section: ------------------------------------------------------------contrasting
confidence: 55%
“…VK2 is a fat-soluble vitamin that is important for human health. Recently, studies have identified various physiological effects possessed by VK2, including glycemic control, anti-vascular calcification, lipid-lowering ability, etc. , Otherwise, numerous reports indicated that VK2 plays a vital role in osteoporosis. Nevertheless, the mechanism of VK2 in T2DOP has not been fully elucidated. Dragh et al found that VK2 is critical in restoring mitochondrial function .…”
Section: Discussionmentioning
confidence: 99%
“…The mice were then divided into two groups: WRS ( n = 8) and control ( n = 8) groups. The WRS method has been previously described in detail [ 9 , 11 , 13 , 14 ]. Briefly, mice were restrained in a 50-mL conical centrifuge tube with multiple punctures and vertically immersed in the xiphoid process in a 24 °C ± 1 °C water bath for 6 h per day, five times per week, for four weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Water-immersion restraint stress (WRS) is a well-characterized chronic stress model. WRS in a mouse model results in diminished BMD [ 9 ], altered tryptophan catabolism [ 10 ], gastric damage [ 11 ], and sleep disturbances [ 12 ]. However, analyzing the impact of repetitive or chronic stress can be challenging, as inbred mice strains frequently become habituated to a given set of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%